The Faktor-Faktor Makroekonomi yang Mempengaruhi Pasar Saham di Amerika Serikat dan Pasar yang berkaitan dengan China: English - Ardika Tristyanto; aminudin Ma'ruf (Jurnal Ekonomika : INDEPENDEN, 2026)
This study analyzes the short-run macroeconomic determinants of stock market dynamics in the United States and a China-related equity market using the Autoregressive Distributed Lag (ARDL) approach. Monthly data are employed for the S&P 500 Index and the Hang Seng Index, along with key macroeconomic variables: Economic Policy Uncertainty (EPU), Consumer Price Index (CPI), Industrial Production Index (IPI), and Bitcoin (BTC) prices. Unit root test results show mixed orders of integration, supporting the use of the ARDL framework. However, bounds testing finds no evidence of cointegration, indicating the absence of a long-run relationship and justifying a focus on short-run dynamics. The findings reveal clear market asymmetries. In the United States, industrial production has a significant negative effect on stock returns, while BTC prices exert a positive and significant influence, reflecting risk-on behavior and liquidity effects. In contrast, EPU in China shows a positive and near-significant effect, suggesting uncertainty is perceived as a signal of potential policy intervention. Inflation remains insignificant in both markets, highlighting structural differences between mature and policy-driven economies. Keywords: S&P 500, Hang Seng Index, Economic Policy Uncertainty, Consumer Price Index, Industrial Productivity Index, Bitcoin, United States and China